Nanocrystals of a New Complex Perovskite Dielectric Ba2TmSbO6 - M. M., Yusoff; Nair, V. M.; Rajan, Jose; Kumar, G. M. Anil; Wariar, P. R. S. (Elsevier Ltd, 2012)
Nanocrystals of a new complex perovskites ceramic oxide, barium thulium antimony oxide – Ba2TmSbO6,were synthesized using a single step auto-ignition combustion process. The combustion product was single phase and composed of aggregates of nanocrystals of sizes in the range 20–50 nm. Ba2TmSbO6 crystallized in cubic perovskite structure with lattice parameter, a = 8.4101A˚ . The polycrystalline fluffy combustion product was sintered to high density (∼97%) at ∼1450 ◦C for 4 h. Resistivity of the sintered specimen was ∼5 M/cm. The Ba2TmSbO6 has dielectric constant (ε) and dielectric loss (tan ı) of 17 and ∼10−4 at 5 MHz; the new material would probably be developed as a low-loss dielectric material.